PENGARUH HUMAN RELATION, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN MANDAILING NATAL - Wahyu Hidayat Siregar; Ahmad Subhan Batubara; Midradiana .; Irmaryanto .; Eliani . (Universitas Islam Sumatera Utara, 2020)
The purpose of this research was to determine and analyze the influence of human relations, work discipline and work environment on the employees performance of Dinas Pengelolaan Keuangan Dan Aset Daerah Kabupaten Mandailing Natal, both partially and simultaneously. The sample in this research were all employees, amounting to 81 people. Determination of the number of samples using a saturated sample (census). The analysis technique used is descriptive analysis method and multiple linear regression analysis with SPSS 20.00 for windows. The results showed that : 1) Human relations had a positive and significant effect on the employees performance of Dinas Pengelolaan Keuangan Dan Aset Daerah Kabupaten Mandailing Natal; 2) Work discipline has a positive and significant effect on the employees performance of Dinas Pengelolaan Keuangan Dan Aset Daerah Kabupaten Mandailing Natal; 3) Work environment has a positive and significant effect on the employees performance of Dinas Pengelolaan Keuangan Dan Aset Daerah Kabupaten Mandailing Natal; 4) Human relations, work discipline and work environment have a positive and significant effect on the employees performance of Dinas Pengelolaan Keuangan Dan Aset Daerah Kabupaten Mandailing Natal. Human relations, work discipline and work environment have the ability to explain its effect on employee performance variables of 64.0%, while the remaining 36.0% is the influence of other independent variables not examined in this research.